The effect of ozone and naringin on intestinal ischemia/reperfusion injury in an experimental model. (September 2015) - Isik, Arda; Peker, Kemal; Gursul, Cebrail; Sayar, Ilyas; Firat, Deniz; Yilmaz, Ismayil; Demiryilmaz, Ismail
Abstract: Background: The aim of the study was to evaulate the effect of ozone and naringin on the intestine after intestinal ischemia-reperfusion(II/R) injury. Methods: Thirty five rats divided into 5 groups of 7 animals: control, II/R, ozone, naringin and naringin + ozone. Only laparotomy and exploration of the superior mesenteric artery (SMA) were done in control group. In the experimental groups, SAM was occluded for 1 h and reperfused for 1 h. 15 min after ischemia, ozone (25 μg/ml, 0.5 mg/kg), naringin (80 mg/kg) and naringin + ozone(80 mg/kg + 25 μg/ml, 0.5 mg/kg) were infused intraperitoneally to each groups. Ileum tissues were harvested to determine intestinal mucosal injury and oxidative stress markers. For SMA occlusion, different than literature, silk suture binding was used. Results: Oxidative stress markers were significantly low in experimental groups compared with II/R group (p < 0.05). Histopathologically, the injury score was significantly low at experimental groups compared with II/R group (p < 0.05). The lowest injury score was encountered at naringine + ozone group. Conclusions: Ozone alone or combined with naringin has a protective effect for mesenteric ischemia. Instead of using instruments such as clamps in the II/R rat model, silk binding may be used safely. Highlights: we want to evaulate the effect of ozone and naringin on the intestine after intestinal ischemia-reperfusion injury. Also for superior mesenteric artery occlusion, different than literature, silk suture binding was used in our study.